EVALUATION OF FAMILY BUSINESS SUCCESSOR CRITERIA: CV. SENTRA MOTOR SPORT - Abdurroziq Naufal; Siti Jahroh; Andina Oktariani, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The family business has a characteristic in which the transfer of leadership is given to one of the family members as the next generation to maintain the continuity of its enterprise. Most family businesses in Indonesia do not yet have its succession plan. One of the keys to a successful selection of prospective business successors is to determine the right leadership criteria. This research aims to (1) identify indicators of successor characteristics, (2) identify leadership criteria, and (3) compose an evaluation of the succession at CV. Sentra Motor Sport (CV.SMS), a family business in the automotive sector located in Bogor, Indonesia. The tools for this research are successor’s characteristics indicator, ACE MAN leadership criteria, and post-succession evaluation. The study employed descriptive-qualitative methods from primary data obtained through in-depth interviews with the predecessor, successor, and the employees of the family business. The total number of respondents were five persons. The interviews were conducted from June to July 2020. The results showed that the indicators of successor characteristics were in accordance with the expectations of the founder. The results of the ACE MAN leadership criteria assessment showed that the most dominant criterion was networking and the smallest ones were charismatic and achieving. According to the post-succession evaluation, the successor’s leadership criteria of CV. Sentra Motor Sport could be categorized as a successful case.